FAKTOR-FAKTOR YANG MEMENGARUHI PRODUKSI CENGKEH DI KABUPATEN TOLITOLI - Marding Marding; Rustam Abd. Rauf; Christoporus Christoporus (Universitas Tadulako, 2020)
This research aim was to determine the influence of various factors on clove production in Tolitoli regency. This research was conducted from September to November 2018. Data were collected from 86 clove farmers who were selected using a simple random method. The data was processed and analyzed using production function of Cobb-Douglass. The results showed that simultaneously, the independent variables (X) significantly influenced the dependent variables (Y) and the coefficient of determination (R2) was 0.89. Partially, four factors significantly influence the cloves production including land area (X1), ZA fertilizer (X3), Phonska (X4), and the labors (X5) whereas the age of the clove is the only factor that did not significantly affect. Keywords: Cloves, Cobb-Douglass and Production Factors.